Konsolidacja demokracji w Europie Środkowo-Wschodniej: Rola społeczeństwa obywatelskiego - Pietrzyk-Reeves, Dorota (Eastern Review, 2017)
The main question of the article is the connection between democratic consolidation in post-Soviet states and civil society development. Even though such a thesis is very popular in political science, it cannot be borne out in present-day policy. And even if we describe democracy as a purely institutional arrangement, it’s impossible to ignore its substantial character. It certainly includes a dynamic civil society and participatory character of political culture. Given these issues, political analysis is very difficult for all researchers, especially because of the variety of traditions and beliefs.